Ciencia-ficción y derechos humanos. Una aproximación desde la complejidad, las tramas sociales y los condicionales contrafácticos - Sánchez Rubio, David (2010)
In this article I explore a possible linkage between the worlds of science-fiction and human rights. There is a science-fiction literature and cinema with a critical and transgresive character, side by side with cheap, commercialized production. Approaching Human Rights and “impossibility principles” as a different way to build our presents by means of fictional futures, such a present may be regarded as a sort of sacrifice. The human condition always appears in a positive or negative fashion in this literature, as well as positions going from recognition of pluralities and differences, to the authoritarian imposition of a single way to be human